The Middle Finger Response. Crowdworkers of the World United in a Gesture (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The Middle Finger Response (2013) is a curated selection of 300+ spontaneous self- portraits of cloud workers I commissioned travelling around one of the most represan- tive crowdsourcing platform: Amazon Mechanical Turk. All the workers in the selection have been paid about 0.5$ in order to take awebcam picture of themselves showing their face, their context and, ultimately, theirmiddle finger response. It's just a cynical but sincere attempt to establish a dialogue between the artist, the public and the crowd dispersed through the new frontiers of leisure, labour and exploitation in the age of the big cloud.WEB PAGE OF THE INSTALLATION: http://www.crowdworkersoftheworldunite.com